Good is stronger than bad for eudaimonic well-being - Martínez-Zelaya, Gonzalo (2022)
Perceived changes in basic beliefs and growth related to life events were examined in three studies. A representative sample (N = 885), a sample of students and their families (N = 291) and a sample of students (N = 245) responded with a list of positive and negative life events, a scale of changes in basic beliefs and a post-traumatic growth scale. Positive events were strongly associated with changes in basic beliefs, while only weak associations were found for negative events. In addition, negative changes in basic beliefs were associated with growth only in negative life events and positive changes in basic beliefs were generally associated with growth.